The The Influence of Economic Factors on Student Motivation and Learning Achievement at Elementary School - Ghaida Safitri, Intan; Muryanto, Rusdiono (International Conference on Elementary Education, 2025)
Education is one of the main pillars in the development of a nation, which plays an important role in forming a competent and qualified generation. However, economic factors are often a significant obstacle for children achieving their full learning potential. This research aims to determine the influence of students' economic factors on their motivation and learning achievement at elementary school level. This research is motivated by the importance of education in forming a competent and qualified generation, but it is often hampered by economic factors. The research method used is a quantitative descriptive method, which involves collecting data through open and closed questionnaires to teachers. The research results show that disadvantaged economic factors can influence students' motivation and learning achievement. This finding is based on data showing that 83% of teacher respondents stated that economic disadvantage could affect student learning achievement. his is due to a lack learning facilities, low self-confidence, lack of parental support, and limited study time due to having to help parents. This research provides important insights for educators and policy makers to design learning strategies that are more inclusive and fair, and pay attention to economic factors as one of the main determinants of achieving learning achievement.